(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
This paper seeks questions regarding embodied relating in the therapeutic encounter through engagement with Merleau Ponty’s Chiasm. It questions whether the term ’embodiment’ incorporates the dynamism and complexity our relating requires or whether it, ironically, perpetuates dualistic thinking.